Biometric Technology in Digital Banking: Insights from Generation Z and Millennials - Herwin Ardianto; Chitra Laksmi Rithmaya; Larasati Ayu Sekarsari (Journal of Business & Banking, 2025)
Biometric technology offers various conveniences and security features that can enhance the user experience of digital banking. This study explores the adoption of biometric technology in digital banking among Indonesian Generation Z and Millennials. Utiliz-ing the Technology Acceptance Model (TAM), we investigate factors influencing atti-tudes, intentions, and actual use of biometrics among 326 respondents. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Findings indicate that perceived usefulness, ease of use, security, and convenience signif-icantly affect user attitudes, intentions, and actual usage. Additionally, perceived use-fulness moderates the relationship between perceived ease of use and attitudes toward biometric adoption. These insights are crucial for financial institutions aiming to en-hance user acceptance of biometric systems, contributing to secure and user-friendly digi-tal banking solutions for younger consumers in Indonesia.